2005
DOI: 10.1038/sj.eye.6701804
|View full text |Cite
|
Sign up to set email alerts
|

Scleral-fixated posterior chamber intraocular lenses in nonvitrectomised eyes

Abstract: Objective To assess the long-term outcome of scleral-fixated sutured posterior chamber intraocular lens (SPCIOL) implantation in non pars plana vitrectomised eyes (1) to evaluate the long-term visual outcome, (2) to identify preoperative risk factors for poor visual outcomes, and (3) to identify the incidence of vitreoretinal complications. Method A retrospective review of 65 eyes, which had not undergone pars plana vitrectomy prior to scleral-fixated SPCIOL implantation. Results In all, 65 eyes of 61 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 18 publications
0
10
0
1
Order By: Relevance
“…Several reports concerning scleral-fixated posterior chamber intraocular lenses (PCIOL) have been reported with mostly favorable results 4891011. However, the surgical technique of scleral-fixated PCIOL insertion is more technically demanding 111213. Histological studies of the anterior segment showed that the best position in these eyes is sulcus fixation 1415.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports concerning scleral-fixated posterior chamber intraocular lenses (PCIOL) have been reported with mostly favorable results 4891011. However, the surgical technique of scleral-fixated PCIOL insertion is more technically demanding 111213. Histological studies of the anterior segment showed that the best position in these eyes is sulcus fixation 1415.…”
Section: Introductionmentioning
confidence: 99%
“…Sutured posterior chamber lenses can provide excellent visual results. 68,69 We have documented that late suture breakage (using 10/0 proline) is an important problem using this technique 70 and have therefore moved away from suturing lenses as a technique of choice. Modern designs of anterior chamber lens implant generally have low levels of complications 71 and are suitable for this patient population.…”
Section: Clinical Managementmentioning
confidence: 99%
“…12 The 4-point Ab externo SFIOL technique used in our study has been described in detail elsewhere. 13 The SFIOL implantation technique, although more advantageous, is associated with a unique set of sightthreatening complications such as retinal detachment, 14 choroidal hemorrhage, 15 endophthalmitis, 16 suture erosion, and SFIOL dislocation. 17 Complete pars plana vitrectomy before SFIOL reduces the rate of long-term risk of retinal detachment to 3% 8 when compared with the incidence reported with lensectomy and anterior vitrectomy, the earlier technique used in managing ectopia lentis.…”
Section: Discussionmentioning
confidence: 99%